Grow, neighbour grow, grow... Neighbour be good! - Enrique Lopez-Bazo; Esther Vaya; Rosina Moreno (European Regional Science Association (ERSA), 1998)
The main objective of this paper is to outline the relevance of regional externalities when explaining growth. The recent literature has already put attention to external economies or spillover effects, although in most cases it has been at firm or sectoral level. However, it is our belief that at least some types of externalities may spill over the somewhat artificial administrative barriers defining regional economies. In this sense, the paper presents a growth model that includes regional spillovers and obtains empirical evidence of their relevance for the EU regions. The methodology to empirically test and estimate regional spillovers using spatial econometrics techniques is proposed as well.Among other results, it is shown the qualitative and quantitative importance of these externalities and their relevance in the appropriate estimation of the technological parameters of the production function. This way, we are able to estimate a larger rate of convergence caused by factors within the regional economy. Besides, a 10% increase in the growth rate of the neighborgs causes a 6% increase in the growth rate of an economy, while a 10% increase in the steady state level of the neighborgs causes a 2% additional growth. The paper also aims at disentangling the sources for such externalities, considering the effects of different inputs at the neighboring regions, such as private and public capital stocks and human capital. Keywords: Regional Externalities, Growth and Convergence, Spatial Econometrics
Keywords: 330